Comparison of Mathematics Learning Outcomes of Seventh Grade Junior High School Students between DL and PBL Models based on Midterm Test Scores - Mau, Elfrida Olo; Tnesi, Stiven Aloysius; Jomar, Guido Stefano; Lakapu, Meryani (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to compare the effectiveness of the Discovery Learning (DL) and Problem-Based Learning (PBL) models on the mathematics learning outcomes of seventh-grade junior high school students, as measured by midterm exam scores. The background of this study is based on the low international achievement of Indonesian students in mathematics and the dominance of conventional approaches in the learning process. The method used is a quantitative comparative approach with a quasi-experimental design. The sample consists of two classes, each receiving either the DL or PBL model. Data were collected through documentation of MTE scores and analyzed using normality, homogeneity, and independent two-sample t-tests. The analysis results showed that both data sets were normally distributed and homogeneous. The t-test yielded a significance value of 0.823 (p > 0.05), indicating no significant difference in mathematics learning outcomes between students taught using the DL model and those taught using the PBL model. The effect size calculation (Cohen’s d = 0.18) indicated a very small effect. These findings indicate that the effectiveness of the two models is relatively balanced, and learning success is more influenced by non-instructional factors such as learning style and student motivation. Therefore, teachers are advised to choose a learning model that suits the characteristics of their students. This study suggests further research with a broader scope and a mixed-methods approach to gain a more comprehensive understanding. These results are important as a reference for selecting contextual learning strategies.